Exaltación y Coronación de la Reina de la Carrera de Enfermería - Llivi Ruilova, Danny Vicente (2024)
On June 10 of the current year, the Exaltation and Coronation of the Queen of the Nursing career of the Faculty of Health and Human Sciences of the UEB took place, which was attended by the Dr. Silvana López Paredes, Dean; teaching staff, students and the Mgtr. María Olalla, coordinator of the Nursing degree. Miss Karol Alexandra Vásquez García is the Queen of the Nursing career 2024, the same one who will participate for the Crown of the Faculty of Health and Human Sciences.